Heat exposure and its health effects among construction site workers - Siti Nor Izzati, Mat Yaacob (2017)
Heat stress is the net load to a worker which could be exposed from the contribution of environmental factors, occupational and personal factor. It can induce the heat stress symptoms such as headache and muscle cramps. This cross-sectional was conducted in the construction site to determine environmental monitoring and personal heat stress assessment. Besides, to identify factors that influence personal heat stress. The instruments used in data collection were QUEST Temp034 Thermal Environment Monitor to measure Wet Bulb Globe Temperature (WBGT) index whereas OMRON Digital HEM7200 Blood Pressure Monitor and Infrared Digital Thermometer were used in this study to assess personal monitoring. Meanwhile, questionnaire was used to retrieve information related to heat stress symptoms. There were a total of 40 respondents participated in this study. This study focus on construction site in Kuantan, Pahang. There was a significant differences between ambient temperature and heat index. It also showed that WBGT was significantly higher than heat index. Apart from that, there was no significant correlation between environmental heat exposure (WBGT) and physiological effect (blood pressure and heart rate). Besides that, factor of hydration status and Body Mass Index (BMI) was significantly influence heat stress level among all the factors as the significant value was (p<.05). The prevalence of heat stress symptoms showed that there was several most common symptoms that frequently suffered by workers at construction site such as headache, weakness, fatigue, dizziness, high body temperature and muscle cramps. In conclusion, high environmental temperature had escalated the risk stress exposure and increase the tendency of getting heat-related illness with introduce the heat stress symptoms.